Recycling of glass cullet as aggregate for clays used to produce roof tiles - Costa, F.B. [UNESP]; Teixeira, S.R. [UNESP]; Souza, A.E. [UNESP]; Santos, G.T.A. [UNESP] (Rede Latino-Americana de Materiais, 2009)
Numerous silicates based wastes have been produced and considered for recycling and reuse. Among them, glass cullet is one of the most common silicate wastes and has considerable volume in the cities wastes. A big amount of this waste is recycled by the glass industry but another part is dumped in the cities garbage deposits. In the last few decades there has been considerable research on the reuse of glass waste as aggregate to produce glass-ceramic, for mortars, ceramics and for cement and concrete. This work is concerned to study the reuse of one way glass bottles as aggregate to produce roof tiles (red ceramic). Two kinds of glass powder were prepared by sieving: alpha (0.088 to 0.125 mm) and beta (0.037 to 0.088 mm). Prismatic ceramic bodies (CB) were pressed (60 x 20 x ~5 mm) using a ceramic mass with 0, 5, 8 and 10 % of glass cullet powder added and fired at five different temperatures (800 to 1200 ºC). The results of the technological tests (flexural strength, water absorption, dimensional changes, density and porosity apparent) show that shrinkage increases with the glass content and all other properties above are improved. These changes are more exhibited at temperatures higher than 900°C and in the higher powder glass concentrations (8 e 10%).
Keywords: roof tiles; glass; one-way bottles; recycling